DETERMINATION OF OPTIMUM CIRCUIT OF MEASUTRING CAPACITANCE CONNECTION TO FREQUENCY CONVERTER OF THICKNESS - Osadchuk, Alexander; Krynotchkin, Roman (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the results of research, dealing with the study of value and place of measuring capacitance connection to frequency converter of thickness, based on negative resistance. The technique of transfer function, measurement range and sensitivity obtaining by means of computer-based experiment of described. The choice of optimum variant of connection, based the analysis of the results obtained is substantiated.